Ruch ludowy w powiecie żagańskim w latach 1945-1949 = Peasant movement in Żagań county in 1945-1949 - Koteluk, Daniel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
An undoubtedly important role in the early post-war management of Żagań county was played by the peasant movement activists. Certainly, the Polish Peasant Movement (Polskie Stronnictwo Ludowe, PSL) had infinitesimal chances of organizational development, compared with the Peasant Movement Stronnictwo Ludowe, SL), because the Polish Workers' Party (Polska Partia Robotnicza, PPR), considering themselves the only authority in this area, made their best to hamper the operations of Mikołajczyk's Polish Peasant Party.
Keywords: Stronnictwo Ludowe; Zjednoczone Stronnictwo Ludowe (ZSL); Kongres Jedności Ruchu Ludowego; Polska - historia - od 1944 r.; Żagań (woj. lubuskie); Żagań - historia